2019
DOI: 10.3390/e21020122
|View full text |Cite
|
Sign up to set email alerts
|

Phases, Microstructures and Mechanical Properties of CoCrNiCuZn High-Entropy Alloy Prepared by Mechanical Alloying and Spark Plasma Sintering

Abstract: In the study, an equiatomic CoCrNiCuZn high-entropy alloy (HEA) was prepared by mechanical alloying (MA) and the phases, microstructures, and thermal properties of the alloy powder were explored. The results suggest that a solid solution with body-centered cubic (BCC) phase and a crystalline size of 10 nm formed after 60 h of milling. Subsequently, the alloy powder was consolidated by spark plasma sintering (SPS) at different temperatures (600 °C, 700 °C, 800 °C, and 900 °C). Two kinds of face-centered cubic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The CoCrNiCuZn HEAs were prepared by Sun et al using a planetary ball mill for 60 h with a BPR and mill speed of 20:1 and 300 rpm, respectively [33]. The fabricated HEAs were consolidated by SPS and their microstructures, phases, and mechanical properties were studied.…”
Section: Preparation Of Heas By Mechanical Alloyingmentioning
confidence: 99%
See 2 more Smart Citations
“…The CoCrNiCuZn HEAs were prepared by Sun et al using a planetary ball mill for 60 h with a BPR and mill speed of 20:1 and 300 rpm, respectively [33]. The fabricated HEAs were consolidated by SPS and their microstructures, phases, and mechanical properties were studied.…”
Section: Preparation Of Heas By Mechanical Alloyingmentioning
confidence: 99%
“…They reported that the fabricated HEA exhibited a crystallite size of 10 nm and a BCC structure after 60 h of milling. After the consolidation of HEA powders by SPS, the authors observed two different FCC phases, as shown in Figure 10, and named them as FCC1 and FCC 2, respectively [33]. They studied the Vickers microhardness and compressive strength of the SPS-consolidated HEA (900 • C) samples, and the values were found to be 615 HV and 2121 MPa, respectively.…”
Section: Preparation Of Heas By Mechanical Alloyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-phase microstructures formed in the alloys, which can be attributed to the large lattice strain and negative enthalpy of mixing, caused by the addition of Zr. Sun et al [ 23 ] also employed the mechanical alloying technique and prepared the CoCrNiCuZn alloy. Pd addition promoted the local- and long-range lattice distortions in CoCrFeNi alloy and also had effect on the phase stability and phase transformation.…”
Section: Mechanical Behaviorsmentioning
confidence: 99%